Biocentro de espiritualidad para la comunidad diocesana de Neiva Huila. (2022)
This degree work proposal is focused on research that aims to determine the importance of interior design through bioclimatic comfort in a spiritual environment, optimizing the diocesan work of the city of Neiva-Huila, and thus, reduce the current deficit, avoiding an increase of improvised spaces, as well as places without any foundation within the context of the Catholic Church. The techniques implemented are: observation and surveys, with the purpose of collecting said information, and articulating them later in the design, based on an analysis that allows me to clarify the questions raised. The research approach that I will develop is an exploratory-descriptive study, where I can address the development of a stage of scientific research, which leads me to establish parameters for the proposed approach, the type or level of research, is based on an exploratory, descriptive study since thus, I compile a search for information with the diocese, what is projected to materialize through formal normative criteria, as well as some elements that are necessary to be established in the design of the bio-center of spirituality. Finally, the interior design proposal is aimed at spiritual environments through bioclimatic comfort, exalting coffee wood as a proposed material, also addressing essential characteristics regarding its functionality, accessibility, environmental conditions, aesthetics, projected in each one of the spaces that make up the approach and thus achieve comfort based on the design of sensory architecture with the necessary aspects for its ecclesiastical identity.